Suggestopedia: The effect in teaching vocabulary for elementary students - Yenita Sarwoningtyas; Testiana Deni Wijayatiningsih; Diana Hardiyanti (Scientific English, 2025)
This study aims to examine the effectiveness of the Suggestopedia method combined with the traditional game “Engklek” in improving the English vocabulary mastery of fifth-grade students at SD IT At-Taqwa Grabag, Magelang. The research design used a quasi-experimental approach with two groups: an experimental class that received treatment using the game-based Suggestopedia method and a control class that was taught using conventional methods. Data were collected through pre-tests, post-tests, and student engagement questionnaires covering behavioural, cognitive, emotional, and affective dimensions. Data analysis used paired sample t-tests, independent t-tests, and descriptive analysis. The results showed that the experimental group experienced a significant increase in vocabulary scores (M = 81.21) compared to the control group (M = 74.48). The t-test confirmed a significant difference (p < 0.05). In addition, students in the experimental class showed high engagement: they actively participated, were focused, enjoyed the learning process, and felt happy and interested. The integration of the traditional game “Engklek” not only made learning more enjoyable but also fostered cultural attachment and reduced dependence on gadgets. This study confirms that Suggestopedia, when combined with local game media, is effective in improving vocabulary mastery while building student engagement. These findings provide practical contributions for English teachers, curriculum designers, and primary education institutions seeking innovative, contextual, and relevant approaches to the needs of Generation Alpha.